Comprehensive Analysis of Sterol O-Acyltransferase 1 as a Prognostic Biomarker and Its Association With Immune Infiltration in Glioma - Guo, Xuyang; Zhou, Shaolong; Yang, Zhuo; Li, Zi-An; Hu, Weihua; Dai, Lirui; Liang, Wulong; Wang, Xinjun (Frontiers in Oncology, 2022)
Metabolic reprogramming is a hallmark of glioma, and sterol O-acyltransferase 1 (SOAT1) is an essential target for metabolic therapy. However, the prognostic value of SOAT1 and its association with immune infiltration has not been fully elucidated. Using RNA-seq and clinical data of glioma patients from The Cancer Genome Atlas (TCGA), SOAT1 was found to be correlated with poor prognosis in glioma and the advanced malignancy of clinicopathological characteristics. Next, the correlation between SOAT1 expression and tumor-infiltrating immune cells was performed using the single-sample GSEA algorithm, gene expression profiling interactive analysis (GEPIA), and tumor immune estimation resource version 2 (TIMER2.0); it was found that SOAT1 expression was positively correlated with multiple tumor-infiltrating immune cells. To further verify these results, immunofluorescence was conducted on paraffin-embedded glioma specimens, and a positive trend of the correlation between SOAT1 expression and Treg infiltration was observed in this cohort. Finally, differentially expressed gene analysis, and Gene Ontology and Kyoto Encyclopedia of Genes and Genomes analyses were performed to explore the biological processes and signaling pathways that SOAT1 may be involved in during glioma pathogenesis. A protein-protein interaction network was established, and co-expression analysis was conducted to investigate the regulatory mechanism of SOAT1 in glioma. To the best of our knowledge, this is the first comprehensive study reporting that SOAT1 may serve as a novel prognostic biomarker associated with immune infiltrates, providing a novel perspective for glioma metabolic therapy.